Evaluation of Inflammatory markers in different stages of Chronic Renal Disease - Farha Khan; Sangeeta Kapoor; Jyoti Rana; Saba Khan (Asian Journal of Medical Sciences, 2022)
Background: Chronic kidney disease (CKD) refers to a long-term loss of kidney function. The progression of CKD leads to the damage of other organs including cardiovascular disease which increased the risk of mortality. Early detection of kidney failure can slow down the end-stage renal disease. Aims and Objectives: To estimate the inflammatory marker Adenosine deaminase (ADA) activity in different stages of CKD. To correlate the level of ADA activity with Serum Creatinine with different stages of CKD on the basis of estimated glomerular filtration rate (eGFR). Materials and Methods: The participants having age more than 18 and <60 years having CKD have been enrolled as a study group. CKD was confirmed by calculating eGFR using Cockcroft-Gault equation, plasma creatinine estimation done in all the patients. This study was approved by the Ethical Committee of TMMC and RC. Results: It is observed that the incidence of CKD reaches its maximum strength during middle age. 28% of the young patients, i.e., 45 years of age or younger at the time of CKD, had increased level of ADA. Serum levels of ADA, Creatinine were higher among participants with lower level of eGFR. Inflammation was higher among those with lower eGFR. All biochemical parameter (ADA, CRP, ESR) shows the negative correlation with eGFR. eGFR shows a negative highly significant correlation withESR with a correlation coefficient of r=−4.702 (P<0.001). Conclusion: With the progression of Kidney disease (CKD stages 1–5) it comes to significantly increase of inflammatory markers as decrease in the eGFR with statistical significance. Inflammatory Biomarkers were inversely associated with the measure of kidney function. It is clear that a single indicator of renal function is not sufficient in evaluating the kidney disease stage.